The Impact of Internship on Soft Skills and Hard Skills to Improve Students' Work Readiness - Ria Sakinah; Meri Dian Nisa; Linda Hariyani; Silviana Hastika Dewi; Mochammad Isa Anshori (Journal of Transformational Human Resource Management, 2025)
This study aims to examine the influence of internship experience on the development of students' soft and hard skills and their impact on job readiness. The method used was a quantitative approach, with a sample of students from Trunojoyo University, Madura, who had participated in internships. The results showed that internship experience significantly improved both types of skills, ultimately contributing positively to improving students' job readiness. Soft and hard skills also act as mediators in this relationship.